DETERMINAN AGRESIVITAS PAJAK: PERAN UKURAN PERUSAHAAN SEBAGAI PEMODERASI - Juniartika, Suci; Junaidi, Junaidi (POLITEKNIK LP3I JAKARTA, 2026)
This study aims to analyze the effect of business strategy, debt to asset ratio (DAR), and sales growth on tax aggressiveness in property and real estate sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2022–2024, with firm size as a moderating variable. The population comprises all property and real estate companies listed on the IDX, with a total sample of 54 companies selected using purposive sampling, resulting in 162 balanced panel observations. This study uses secondary data obtained from annual reports and financial statements accessed via idx.co.id. The data analysis method employs panel data regression using the Common Effect Model (CEM) selected based on the Chow test, Hausman test, and Lagrange Multiplier test. Tax aggressiveness is measured using the Effective Tax Rate (ETR). The results show that business strategy (PPEINT) has a significant positive effect on tax aggressiveness, while DAR and sales growth have no significant effect. Firm size as a moderating variable strengthens the effect of DAR on tax aggressiveness (M2 significant at p=0.0179), but does not significantly moderate the effect of business strategy (M1) and sales growth (M3) on tax aggressiveness. These findings suggest that internal company factors, particularly business strategy and capital structure moderated by firm size, play an important role in determining tax aggressiveness behavior in the property and real estate sector.